# Prove that 1/(1-tanx) - 1/(1+tanx) = tan2x .

### 1 Answer | Add Yours

To add the ratios, we'll have to have the same denominator. We'll calculate the least common denominator for the given ratios.

LCD = (1-tanx)(1+tanx)

We notice that the LCD is a difference of square:

LCD = 1 - (tan x)^2

To obtain the denominator 1 - (tan x)^2, we'll multiply the first ratio by (1+tanx) and the second ratio, by (1-tanx).

We'll re-write the left side:

1/(1-tanx) - 1/(1+tanx) = (1 + tan x - 1 + tan x)/[1 - (tan x)^2]

We'll eliminate and combine the like terms from numerator:

**1/(1-tanx) - 1/(1+tanx) = 2tan x/[1 - (tan x)^2]** (1)

Now, we'll re-write the right side:

tan 2x = tan (x+x)

We'll apply the formula for the tangent of the sum of 2 angles:

tan (x+x) = (tan x + tan x)/(1-tan x*tan x)

**tan 2x = 2tan x/[1 - (tan x)^2] **(2)

**We notice that we have obtained (1) = (2), so the identity is verified, fro any value of x:**

**1/(1-tanx) - 1/(1+tanx) = 2 tan x**